Itu Analisis Sosialisasi Wakaf Produktif untuk Pemberdayaan Ekonomi Sosial (Studi Kasus : Yayasan Wakaf Cendekia Indonesia) - Rian Gustandi; Franciskus Antonius Alijoyo (Universitas Pasundan, 2025)
Problems arise such as, some programs have not been able to reach their fundraising targets, because Human Resources (HR) are overwhelmed in carrying out each program. The benefits of the waqf program have not been fully felt by donation recipients and donors, and productive waqf profits have not been able to fund the running of the education sector, and the management of social media or websites for waqf outreach has not been optimal. Based on this background, a solution is needed, Analysis of Productive Waqf Socialization for Social Economic Empowerment (Case Study: Indonesian Scholars Waqf Foundation). As a goal, fundraising can achieve targets, prioritize programs that are already running optimally, more effectively carry out waqf socialization both digitally and technically, and be able to adjust socialization methods based on targets (donors) in the hope of being able to increase generous investors through productive and effective waqf socialization. In the future, productive waqf profits will be able to realize free education programs.